Understanding the Drivers’ Factors for Choosing an Accounting Student’s Career as A Professional Accountant - Frihardina Marsintauli; Roni Patar Situmorang; Susi Ratna Suminar (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2022)
A career is a person's main goal in obtaining education in the field of interest. Students who choose an accounting major certainly want to have a career related to accounting. However, a student's choice of major may not be following the career he is involved in. This research examines the effect of intrinsic value, career prospects, labor market considerations, work environment, financial rewards, and individuals on the career selection of accounting students as a public accounting profession. The object of this research is undergraduate accounting students at Binus Online Learning. The sampling technique used is the Slovin technique, with a total sample of 171 respondents. Data collection techniques were taken by distributing questionnaires using Google Form Link and distributed through electronic media. The analytical method used is Multiple Linear Regression analysis with the SPSS analysis tool. The result showed that the variables of intrinsic value, career prospects, labor market considerations, work environment, financial rewards, and individuals have a significant effect on the career choices of accounting students to become public accounting profession. With the low attractiveness of the public accounting profession among accounting students themselves, public accounting professional organizations and academics can recommend encouraging students to take the Certified Public Accountant (CPA) exam, namely supporting, and helping students who really intend to have a career as public accountants and encourage them not to change their career choices. The results of this study are input to the university that it is necessary to introduce the accounting profession, students who hear and follow the development of accounting science in the form of seminars or share knowledge from lecturers will provide an overview and motivation for students to choose a career as an accountant